Comparison of semi‐empirical and density functional approaches for the colour and constitution of anthraquinone dyes using X‐ray structure. (23rd March 2022) - Hwang, Ji‐yong; Kim, Sunghoon; Matsumoto, Shinya
Abstract: Theoretical calculations with density functional theory, semi‐empirical PM5 random phase approximation and Zerner's intermediate neglect of differential overlap CI were carried out for various amino and hydroxy anthraquinones using X‐ray structure data. Comparing quantum chemical calculation results based on X‐ray structure, the PM5 random phase approximation method was the most promising for the prediction of λ max for anthraquinone dyes among the computational methods studied here. From the results of calculated gross population, pz, it was found that the value of pz using the time‐dependent density functional theory method was greater than the values calculated by semi‐empirical methods. The overestimation of pz could be attributed to the incorrect density functional theory calculation results. The results of PM5 random phase approximation‐calculated oscillator strength and torsion angle showed reasonable agreement with the observed results for sterically hindered anthraquinone dyes.